Popular Egyptian cinema : gender, class, and nation - Shafik, Viola, 1961- (American University in Cairo Press, 2007)
Viola Shafik examines popular and commercial movies from Egypt's film industry, including a number of the biggest box-office hits widely distributed in Egypt and the Arab world. She examines these films against the backdrop of the country's overall socio-political development, from the emergence of the film industry in the 1930s, through the Nasser and Sadat eras, up to the era of globalization.
Keywords: Motion pictures -- Social aspects -- Egypt -- History.; Motion pictures -- Egypt -- History.; Sex role in motion pictures.; Social classes in motion pictures.; National characteristics in motion pictures.; Cinéma -- Aspect social -- Égypte -- Histoire.; Cinéma -- Égypte -- Histoire.; Rôle selon le sexe au cinéma.; Classes sociales au cinéma.; Caractéristiques nationales au cinéma.; PERFORMING ARTS -- Reference.; PERFORMING ARTS -- Film & Video -- Reference.; Motion pictures -- Social aspects; Motion pictures; National characteristics in motion pictures; Sex role in motion pictures; Social classes in motion pictures; Egypt; Film; Ägypten; Massenkultur; History